Trabzon’dan Ahşap Bir Cami Örneği: Of – Bölümlü Mithat Paşa Camii / A Wooden Mosque from Trabzon: Of – Bolumlu Mithat Pasha Mosque - Aydın, Hasan; Perker, Sevgen Z. (Journal of History Culture and Art Research, 2017)
Abstract Trabzon, which is located on the shore of Black Sea and one of the oldest centers in Anatolia, has included many cultural heritage factors due to its historical importance and background. Mosques have an important role in shaping cultural heritage of the region. One of them is a wooden mosque which located in Bolumlu suburban area at Of District in Trabzon province. The wooden mosque is one of the historical and important models in Anatolia in terms of wooden material use in the traditional architecture. The wooden material which has an important role in Black Sea Region’s building culture was widely and ingeniously used on bearing systems and other components of Bolumlu Mithat Pasha Mosque. The objective of this study is to examine and promotion of this mosque’s architectural properties and discussion of current situation of this mosque. Öz Trabzon, geçirdiği tarihsel süreç nedeniyle çok sayıda kültürel miras unsurunu bünyesinde barındırmaktadır. Sözü edilen kültürel miras unsurlarından bir tanesi de Trabzon’un Of İlçesi’ne bağlı Bölümlü Beldesi, Mithatpaşa Mahallesi’nde bulunan ve geleneksel mimaride ahşap kullanımının Anadolu’daki tarihi ve önemli örneklerinden bir tanesi olan camidir. Karadeniz Bölgesi yapı kültürü için önemli bir malzeme olan ahşap, Of Bölümlü Mithat Paşa Camii’nin hem taşıyıcı sisteminde hem de diğer elemanlarında ustalıkla kullanılmıştır. Söz konusu tarihi yapının mimari özelliklerinin araştırılması, tanıtılması ve güncel durumunun değerlendirilmesi bu çalışmanın amacını oluşturmaktadır.